2022
DOI: 10.3390/ma15176156
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Ti6Al4V/Silk Fibroin Composite for Load-Bearing Implants: A Hierarchical Multifunctional Cellular Scaffold

Abstract: Despite the tremendous technological advances that metal additive manufacturing (AM) has made in the last decades, there are still some major concerns guaranteeing its massive industrial application in the biomedical field. Indeed, some main limitations arise in dealing with their biological properties, specifically in terms of osseointegration. Morphological accuracy of sub-unital elements along with the printing resolution are major constraints in the design workspace of a lattice, hindering the possibility … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 71 publications
0
4
0
Order By: Relevance
“…Furthermore, it has been demonstrated that substrates having elastic moduli within the range of 25-40 kPa promote an upregulation of osteocalcin expression and induce mesenchymal stem cell differentiation towards osteoblasts [66]. Alternatively, SF-based soft materials with good biological properties can be used as fillers in combination with any load-bearing material, i.e., titanium lattice structures [67].…”
Section: Preliminary In Vitro Biological Testmentioning
confidence: 99%
“…Furthermore, it has been demonstrated that substrates having elastic moduli within the range of 25-40 kPa promote an upregulation of osteocalcin expression and induce mesenchymal stem cell differentiation towards osteoblasts [66]. Alternatively, SF-based soft materials with good biological properties can be used as fillers in combination with any load-bearing material, i.e., titanium lattice structures [67].…”
Section: Preliminary In Vitro Biological Testmentioning
confidence: 99%
“…As one can picture the strength of spider webs seen in daily life, silk fibroin is a natural protein with outstanding mechanical properties. As a result, it has been popularly used in load-bearing scenarios such as bioresorbable bone fixation devices [148,149], load-bearing scaffolds for dermal tissue regeneration [150] and bone regeneration [151]. In addition, due to its excellent biocompatibility, superb flexural strength, and good elasticity, numerous of SF-based NGCs have been developed and encouraging outcomes have been achieved [54,[152][153][154].…”
Section: Proteinsmentioning
confidence: 99%
“…Silk fibroin has emerged as a biopolymer with superior potential application value in tissue engineering and regenerative medicine [ 1 ], owing to its biocompatibility, processability, and relatively mild processing conditions [ 2 , 3 ]. Various types of silk-based materials that undergo reprocessing, modification, and modulation are used in numerous areas, such as tissue engineering [ 4 ], drug delivery [ 5 ], 3D printing [ 6 ], cell coating [ 7 ], microfluidics [ 8 ], biosensors [ 9 ], and blood vessels [ 10 ]. Nevertheless, one of the major challenges for these silk-based biomaterials is safety and efficacy in vivo tissue healing [ 11 ].…”
Section: Introductionmentioning
confidence: 99%